Understanding Parricide : When Sons and Daughters Kill Parents - Heide, Kathleen M. (Oxford University Press, 2013)
"Understanding Parricide is the most comprehensive book available about juvenile and adult sons and daughters who kill their parents. Dr. Heide moves far behind the statistical correlates of parricide by synthesizing the professional literature on parricide in general, matricide, patricide, double parricides, and familicides. As a clinician, she explains the reasons behind the killings. Understanding Parricide includes in-depth discussion of issues related to prosecuting and defending parricide offenders. The book is enriched with its focus on clinical assessment, case studies, and follow-up of parricide offenders, as well as treatment, risk assessment, and prevention."--Publisher's website.